2010
DOI: 10.1186/1741-7015-8-84
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the evidence relating FEV1decline to giving up smoking

Abstract: BackgroundThe rate of forced expiratory volume in 1 second (FEV1) decline ("beta") is a marker of chronic obstructive pulmonary disease risk. The reduction in beta after quitting smoking is an upper limit for the reduction achievable from switching to novel nicotine delivery products. We review available evidence to estimate this reduction and quantify the relationship of smoking to beta.MethodsStudies were identified, in healthy individuals or patients with respiratory disease, that provided data on beta over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
77
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 194 publications
10
77
1
2
Order By: Relevance
“…An association with smoking in this regard was not investigated. This impairment is clearly pathological when compared to the findings of a recent, detailed systematic review of 47 studies in healthy individuals or patients with respiratory disease performed by Lee et al These authors measured a FEV1 decline in active smokers of over 40 ml per year compared to less than 30 ml year in never smokers [32]. Notably, the FEV1 decline in Fabry patients, irrespective of their smoking status, 8 8 appears to be of the same order of magnitude of active smokers not affected with FD.…”
Section: Smokingmentioning
confidence: 89%
“…An association with smoking in this regard was not investigated. This impairment is clearly pathological when compared to the findings of a recent, detailed systematic review of 47 studies in healthy individuals or patients with respiratory disease performed by Lee et al These authors measured a FEV1 decline in active smokers of over 40 ml per year compared to less than 30 ml year in never smokers [32]. Notably, the FEV1 decline in Fabry patients, irrespective of their smoking status, 8 8 appears to be of the same order of magnitude of active smokers not affected with FD.…”
Section: Smokingmentioning
confidence: 89%
“…In contrast, it has been clearly demonstrated that continuing exposure to smoke considerably accelerates disease progression, independently of its initial stage 12,57 . The effect of reduction of other risk factors has not been studied in detail; however, it is expected to be associated with a positive impact on the patient.…”
Section: Treatment Strategymentioning
confidence: 97%
“…Elimination of risks (1 st step): Smoking cessation significantly decelerates the declination in lung function 4,5,56,57 . In contrast, it has been clearly demonstrated that continuing exposure to smoke considerably accelerates disease progression, independently of its initial stage 12,57 .…”
Section: Treatment Strategymentioning
confidence: 99%
“…2). These components in turn contribute to chronic cough and sputum production that ultimately leads to a decrease in the forced expiratory volume in 1 s (FEV 1 ) compared with predicted FEV 1 (18).…”
mentioning
confidence: 99%